PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. RAHAYU SUMBER ELECTRIC CISOKA KABUPATEN TANGERANG - Muhammad Raffi; Indra Januar Rukmana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Work Motivation (X1) and Physical Work Environment (X2) on Employee Performance (Y) at PT. Rahayu Sumber Electric. This study uses a quantitative method with an associative approach, which aims to determine the relationship between the independent and dependent variables. The sampling technique used is a saturated sampling technique, with data collection through observation and questionnaires involving 60 respondents. The results of the study partially show that the variable Work Motivation (X1) on Employee Performance (Y) has a regression of Y = 32.189 + 0.234X1 with a correlation coefficient of 0.076, indicating a strong relationship with a determination coefficient of 23.1%. The hypothesis test shows t count > t table (5.646 > 1.671), so Ho is rejected and H1 is accepted, meaning there is a significant influence between Work Motivation on Employee Performance. Other partial results show that the Physical Work Environment (X2) on Employee Performance (Y) has a regression equation of Y = 28.539 + 0.321X2 with a correlation coefficient of 0.341 indicating a low relationship, with a determination coefficient of 34.1%. The hypothesis test shows that the calculated t value is > t table (2.789 > 1.671), so Ho is rejected and H2 is accepted, meaning there is a significant influence between the Physical Work Environment and Employee Performance. Simultaneously, the variables of Work Motivation (X1) and Physical Work Environment (X2) on Employee Performance (Y) show the results of the regression equation of Y = 23.123 + 0.165X1 + 0.285X2 with a correlation coefficient of 0.373 indicating a low relationship with a determination coefficient of 37.3% while 62.7% is influenced by other factors. The hypothesis test shows that the calculated F value is > F table (4.606 > 1.672), so Ho is rejected and H3 is accepted. This means there is a significant simultaneous influence between Work Motivation and the Physical Work Environment on Employee Performance at PT. Rahayu Sumber Electric.